2016
DOI: 10.1111/tpj.13291
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the missing phosphatase on the riboflavin biosynthesis pathway in Arabidopsis thaliana

Abstract: Despite the importance of riboflavin as the direct precursor of the cofactors flavin adenine dinucleotide (FAD) and flavin mononucleotide (FMN), the physiologically relevant catalyst dephosphorylating the riboflavin biosynthesis pathway intermediate 5-amino-6-ribitylamino-2,4(1H,3H) pyrimidinedione 5'-phosphate (ARPP) has not been characterized from any organism. By using as the query sequence a previously identified plastidial FMN hydrolase AtcpFHy1 (At1g79790), belonging to the haloacid dehalogenase (HAD) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 47 publications
2
36
0
Order By: Relevance
“…Taken together, these experiments definitively pinpointed the bacterial metabolite necessary to generate activating MAIT cell ligands as 5‐A‐RU. These studies have now been recapitulated for E. coli and S. pneumoniae by other groups, and also demonstrate the requirement for ribD/G in these bacteria …”
Section: Discovery Of Mr1 Bound Antigens That Activate Mait Cellssupporting
confidence: 56%
See 1 more Smart Citation
“…Taken together, these experiments definitively pinpointed the bacterial metabolite necessary to generate activating MAIT cell ligands as 5‐A‐RU. These studies have now been recapitulated for E. coli and S. pneumoniae by other groups, and also demonstrate the requirement for ribD/G in these bacteria …”
Section: Discovery Of Mr1 Bound Antigens That Activate Mait Cellssupporting
confidence: 56%
“…A further complication is that the enzyme nomenclature also differs among bacteria. The details of riboflavin synthesis and its regulation are complex and still emerging, with the recent discovery of the 5‐A‐RU 5′‐phosphate phosphatase in Arabidopsis thaliana, completing the pathway.…”
Section: Discovery Of Mr1 Bound Antigens That Activate Mait Cellsmentioning
confidence: 99%
“…(Haase et al, 2013;Sarge et al, 2015). The protein AtPyrP2 from Arabidopsis thaliana was found to be very specific for ARPP and silencing of the AtPyrP2 gene led to decreased levels of riboflavin, RP and FAD (Sa et al, 2016). This finding suggests that in plants a riboflavin pathway-specific ARPP phosphatase is present.…”
Section: Ta B L E 1 Substrate Profiles Of Recombinant Roscmentioning
confidence: 96%
“…A study from 2011 showed that an FMN-specific hydrolase (AtcpFHy1) from the HAD superfamily was able to catalyze the dephosphorylation of FMN [46]. A few years later, in 2016, the plastidic FMN hydrolase AtcpFHy1 (At1g79790) together with the gene products of At4g11570 and At4g25840, were identified as having ArPP phosphatase activity [47]. In 2015, the HAD superfamily phosphatase EFI-501083 from Bacteroides thetaiotaomicron (B. thetaiotaomicron) was predicted to catalyze the dephosphorylation of ArPP according to covalent docking models [48].…”
Section: Key Enzymes For the Synthesis Of Rfmentioning
confidence: 99%